Angrynomics - Lonergan, Eric; Blyth, Mark 1967- (Agenda Publishing, 2023)
Why are measures of stress and anxiety on the rise, when economists and politicians tell us we have never had it so good? While statistics tell us that the vast majority of people are getting steadily richer the world most of us experience day-in and day-out feels increasingly uncertain, unfair, and ever more expensive. In Angrynomics, Eric Lonergan and Mark Blyth explore the rising tide of anger, sometimes righteous and useful, sometimes destructive and ill-targeted, and propose radical new solutions for an increasingly polarized and confusing world. Angrynomics is for anyone wondering, where the hell do we go from here?